If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 = 8x + -21 Reorder the terms: 3 + 6x = 8x + -21 Reorder the terms: 3 + 6x = -21 + 8x Solving 3 + 6x = -21 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 3 + 6x + -8x = -21 + 8x + -8x Combine like terms: 6x + -8x = -2x 3 + -2x = -21 + 8x + -8x Combine like terms: 8x + -8x = 0 3 + -2x = -21 + 0 3 + -2x = -21 Add '-3' to each side of the equation. 3 + -3 + -2x = -21 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = -21 + -3 -2x = -21 + -3 Combine like terms: -21 + -3 = -24 -2x = -24 Divide each side by '-2'. x = 12 Simplifying x = 12
| 6x+4x+2= | | x=2/3x18 | | 6+3=8x-21 | | -6x^2+4x+8=0 | | h/-3=6 | | 9n^2-10=125 | | -3(1-3y)+2y= | | (10x-23)=(3x+19) | | 6a^2+4=220 | | 7-d=1 | | x-886/(-5)=-15 | | 78-2x=94-3x | | 2a+6p=20 | | 2(6y-8)= | | 16-2+3-4= | | 7z-6z-z+z=19 | | 27n+(-63)=720 | | 69-x=81-2x | | 4(7x-3x)=7(4-2x) | | 8v+v+4v+2v-14v=20 | | 8(n+1)= | | 7x+14-3x= | | 1b-3y=11 | | 2n+6(n)=-72 | | d-d+3d=3 | | -5+8x-3x+4-4x=5 | | 2x+3=8x+14 | | 2y-y=18 | | 6-7y-2y-8= | | -3m-32m+12= | | -6m+20m+-2m+-17m=5 | | 2x+3=8x+15 |